What are the Key Determinants of Human Resource Management Effectiveness in Enhancing Organizational Financial Performance? - Rosyafah, Siti; Pudjowati, Juliani (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
This study aims to investigate the key determinants of Human Resource Management (HRM) effectiveness and their implications for organizational financial performance. A structured literature review methodology was employed to synthesize findings from various academic databases and sources, including Google Scholar, JSTOR, ScienceDirect, and business-focused databases like Business Source Premier. Keywords such as